2017
DOI: 10.3390/molecules22122212
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Methyl and Phenyl Substituted Stannylene Units into Oligosilanes. The Influence on Optical Absorption Properties

Abstract: Molecules containing catenated heavy group 14 atoms are known to exhibit the interesting property of σ-bond electron delocalization. While this is well studied for oligo- and polysilanes the current paper addresses the UV-absorption properties of small tin containing oligosilanes in order to evaluate the effects of Sn–Si and Sn–Sn bonds as well as the results of substituent exchange from methyl to phenyl groups. The new stannasilanes were compared to previously investigated oligosilanes of equal chain lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…12–15 We argue, however, that ‘truly mixed’ oligomers 16 with both E and E′ in their backbones also deserve thorough investigation, because here a particularly pronounced effect of the different properties of E and E′ on the electronic structure of the oligomeric scaffold can be anticipated. 17…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12–15 We argue, however, that ‘truly mixed’ oligomers 16 with both E and E′ in their backbones also deserve thorough investigation, because here a particularly pronounced effect of the different properties of E and E′ on the electronic structure of the oligomeric scaffold can be anticipated. 17…”
mentioning
confidence: 99%
“…[12][13][14][15] We argue, however, that 'truly mixed' oligomers 16 with both E and E 0 in their backbones also deserve thorough investigation, because here a particularly pronounced effect of the different properties of E and E 0 on the electronic structure of the oligomeric scaffold can be anticipated. 17 Recently, our group has shown that the Si 2 Cl 6 /[nBu 4 N]Cl silylation system, 18 which generates [SiCl 3 ] À as the reactive intermediate, 19,20 can be used in combination with R 2 GeCl 2 for the efficient synthesis of mixed Si,Ge-oligomers. Specifically, we prepared open-chain species (Cl 3 Si) 4 Ge 21,22 or Cl 3 Si-(R 2 Ge) n -SiCl 3 (n = 1, 2; R = Ph, nBu) and applied them as precursors in the chemical vapor deposition (CVD) of Si x Ge 1Àx alloys after hydrogenation.…”
mentioning
confidence: 99%